2020
DOI: 10.1039/c9cy02395j
|View full text |Cite
|
Sign up to set email alerts
|

Pd–Au bimetallic catalysts supported on ZnO for selective 1,3-butadiene hydrogenation

Abstract: The effect of the ZnO morphology on the properties of Pd–Au bimetallic catalysts has been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…[25][26][27] Meanwhile, Pd nanoparticles (NPs) has a higher electron trapping capability than Au and Ag NPs and consequently improves photocatalytic activity by inhibiting the recombination of photoinduced electron-hole pairs. [28][29][30] Hence, the combination of ZnO with noble metals to form noble metal/semiconductor hybrid nanostructures has been proposed as an efficient way to increase photocatalytic efficiency. [31][32][33] Bimetallic (such as AuPd, 24,[28][29][30]34,35,42 AuPt, [36][37][38][39] AgPd 40,41 ) NPs couple with semiconductors have better performance in comparison with monometallic NPs due to the synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Meanwhile, Pd nanoparticles (NPs) has a higher electron trapping capability than Au and Ag NPs and consequently improves photocatalytic activity by inhibiting the recombination of photoinduced electron-hole pairs. [28][29][30] Hence, the combination of ZnO with noble metals to form noble metal/semiconductor hybrid nanostructures has been proposed as an efficient way to increase photocatalytic efficiency. [31][32][33] Bimetallic (such as AuPd, 24,[28][29][30]34,35,42 AuPt, [36][37][38][39] AgPd 40,41 ) NPs couple with semiconductors have better performance in comparison with monometallic NPs due to the synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The zinc oxide (ZnO) supported Pd–Au BMC also have been developed and targeted for selective hydrogenation of 1,3-butadiene where the reaction performance completely relies on shape of ZnO support (Table , entry 17). In this work, the needle shaped ZnO (ZnO-n) support was found slightly more active than tetrapod shaped (ZnO-t) under studied catalyst reduction temperatures (i.e., 523 K, 623 K) and Pd–Au bimetallic combination leads to a slight improvement in selectivity toward the trans -2-butene product . To achieve the highest catalytic performance, various metal hydroxides have also been targeted as catalytic support, which led to some interesting organic transformations in an efficient way.…”
Section: Types Of Catalytic Supports and Their Effects In Organic Tra...mentioning
confidence: 93%
“…Bachiller-Baeza et al prepared bimetallic PdAu-ZnO-n and PdAu-ZnO-t catalysts with 0.3-0.4 Au : Pd mole ratio using two differently shaped ZnO supports (needles ZnO-n and tetrapods ZnO-t) by wet impregnation method. 86 They found that both bimetallic PdAu-ZnO-n and PdAu-ZnO-t catalysts displayed the similar BD conversion and selectivity in the selective BD hydrogenation reaction. 86 The BD conversions and butene selectivities over PdAu-ZnO-n and PdAu-ZnO-t were 92% and 23%, and 99% and 32%, respectively, at 40 C. 86 Hugon et al compared the catalytic properties of Al 2 O 3 supported bimetallic DP-Au/Pd(90) and monometallic DP-Au catalysts for the selective BD hydrogenation reaction.…”
Section: Catalytic Performancementioning
confidence: 99%
“…86 They found that both bimetallic PdAu-ZnO-n and PdAu-ZnO-t catalysts displayed the similar BD conversion and selectivity in the selective BD hydrogenation reaction. 86 The BD conversions and butene selectivities over PdAu-ZnO-n and PdAu-ZnO-t were 92% and 23%, and 99% and 32%, respectively, at 40 C. 86 Hugon et al compared the catalytic properties of Al 2 O 3 supported bimetallic DP-Au/Pd(90) and monometallic DP-Au catalysts for the selective BD hydrogenation reaction. 87 The results showed that bimetallic DP-Au/Pd(90) catalyst presented better catalytic active than the monometallic DP-Au catalyst: BD conversion is reached 100% at 120 C and 170 C, respectively.…”
Section: Catalytic Performancementioning
confidence: 99%